2022
DOI: 10.7759/cureus.25225
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Epidural Dexmedetomidine, Fentanyl, and Tramadol as Adjuvant to Levobupivacaine for Lower Limb Orthopedic Surgeries

Abstract: Background Dexmedetomidine, fentanyl, and tramadol as an adjuvant to local anesthetics improve postoperative analgesia when used in epidural anesthesia. We aimed to compare the efficacy of dexmedetomidine, fentanyl, and tramadol as an adjuvant to levobupivacaine in epidural anesthesia. Materials and methods This was a double-blinded randomized clinical trial (RCT). One-hundred twenty patients of either sex, aged 18-60 years, American Society of Anesthesiologists (ASA) physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Many adjuvants were tried in this context, including alpha-2 adrenoreceptor antagonists such as clonidine and dexmedetomidine, steroids like dexamethasone, antiinflammatory agents, and others. 26 Previous studies have demonstrated the efficacy of perineural dexmedetomidine in prolonging analgesic duration in brachial plexus block, 27 lower limb block, 28 epidural block, 29 and paravertebral block. 30,31 On the other hand, few studies investigated the value of adjuncts to LA in interfascial place block techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Many adjuvants were tried in this context, including alpha-2 adrenoreceptor antagonists such as clonidine and dexmedetomidine, steroids like dexamethasone, antiinflammatory agents, and others. 26 Previous studies have demonstrated the efficacy of perineural dexmedetomidine in prolonging analgesic duration in brachial plexus block, 27 lower limb block, 28 epidural block, 29 and paravertebral block. 30,31 On the other hand, few studies investigated the value of adjuncts to LA in interfascial place block techniques.…”
Section: Discussionmentioning
confidence: 99%